Strut and tie model optimization for reinforced concrete bridge pier head structure using a genetic algorithm - Bambang Piscesa; Tavio Tavio (Institut Teknologi Sepuluh Nopember (ITS), 2020)
Strut and tie model (STM) is more suitable to design the pierhead structures which resist high shear forces transferredfrom the girders. These pierhead structures behave like the disturbed regions as in reinforced concrete deep beam. The designof the struts and ties elements requires the initial geometry configuration of the truss model where its boundaries are limited bythe shape of the pier head structures. To find the optimum topological shape of the truss model, the genetic algorithm (GA)optimization technique is used in this paper. The objective functions in the GA optimization consisted of minimizing the usageof concrete and steel reinforcement material and ensuring all the stress ratios of the strut and tie elements are less than equalto unity. Both prestressed and non-prestressed pierheads are investigated in this paper. The use of prestressing in the pierheadstructures reduces the stresses in the main tension tie significantly. Some shear tie and compression struts members also havealmost zero stresses due to the presence of prestressing forces. For these elements with zero stresses, the elements can beremoved and reduces the concrete and rebar materials usage. Furthermore, the genetic algorithm optimization is found to besuccessful to ensure all the stress ratio in the members to be less than equal to unity.